Nursing Interventions for Biofilm Treatment and Control in People with Chronic Wounds (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To map the actions performed by nurses related to the control and treatment of biofilm in individuals with chronic wounds. Method: Scoping review following the JBI guidelines. The search was performed across four databases, and Google Scholar (as a source of Gray Literature), using the PCC framework as inclusion criteria: Participants: People with chronic wounds; Concept: Biofilms in chronic wounds; Context: Nursing care, with no language or time frame restrictions. A total of 572 publications were identified and, after the eligibility criteria were applied by two independent reviewers, 20 studies were included in the review. Results: The studies selected, published between 2006 and 2021, were predominantly in English. Of these, nine were narrative reviews, two were randomized clinical trials, and one was a systematic review. The treatment and control actions identified included debridement techniques and use of products such as polyhexamethylene biguanide, silver, and iodine, as well as negative pressure wound therapy and ultrasound. Conclusion: The actions identified mainly focus on wound care without prioritizing a comprehensive assessment of the individual. Given the nature of the publications, there is a need for further research with more robust scientific evidence and a broader, more holistic approach to care.